2018
DOI: 10.1073/pnas.1715250115
|View full text |Cite
|
Sign up to set email alerts
|

Glassy dynamics of landscape evolution

Abstract: SignificanceSoil is apparently solid as it moves downhill at glacial speeds, but can also liquefy from rain or earthquakes. This behavior is actually similar to that of glass, which creeps very slowly at low temperatures but becomes a liquid at higher temperatures. We develop a discrete granular-physics hillslope model, which shows that the similarities between soil and glass are more than skin deep. Despite the geologic and climatic complexity of natural environments, the shapes and erosion rates of hillsides… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 75 publications
2
47
0
Order By: Relevance
“…These two hypotheses are supported by the fact that, to the authors' knowledge, this class of creep does not occur in DEM simulations, which use a Cundall‐Strack model (Cundall & Strack, ) or similar Coulomb‐like yield criterion for the frictional forces between grains, and fluctuating forces or slow variations in grain‐grain friction are not included. Some DEM studies have observed creeping below a macroscopic yield criterion like the angle of response (Ferdowsi et al, ), but the results from these studies seem to always include some region of μ>μs.…”
Section: Yield and Flow Of Dense Granular Media In The Context Of Sedmentioning
confidence: 99%
See 1 more Smart Citation
“…These two hypotheses are supported by the fact that, to the authors' knowledge, this class of creep does not occur in DEM simulations, which use a Cundall‐Strack model (Cundall & Strack, ) or similar Coulomb‐like yield criterion for the frictional forces between grains, and fluctuating forces or slow variations in grain‐grain friction are not included. Some DEM studies have observed creeping below a macroscopic yield criterion like the angle of response (Ferdowsi et al, ), but the results from these studies seem to always include some region of μ>μs.…”
Section: Yield and Flow Of Dense Granular Media In The Context Of Sedmentioning
confidence: 99%
“…However, as discussed in this section, the granular material itself may be partially responsible. In fact, it is well known that granular creep can be observed in a variety of observational geophysical contexts (Boulton & Hindmarsh, 1987;Ferdowsi et al, 2018;Pierson et al, 1987) as well as more idealized granular flows in a laboratory setting (Amon et al, 2013;Komatsu et al, 2001;Moosavi et al, 2013;Nichol et al, 2010;Roering et al, 2001), including sediment transport explicitly (Allen & Kudrolli, 2018;Houssais et al, 2015), as depicted in Figure 2. Generally, creeping refers to slow, typically intermittent flow (not limited to the bed surface) that occurs below a macroscopic yield criterion.…”
Section: Creep and Nonlocal Rheologiesmentioning
confidence: 99%
“…Other possible phenomena in complex systems where the characteristics of the onset of chaos may appear in ways similar to those illustrated here are: (1) Protein folding [55], traffic jams [56] and hill slope evolution [57] are processes that display glassy dynamics and could be modelled via the bifurcation gap. (2) Critical fluctuations in many kinds of systems, like, to give one example, in spatial complex networks [58].…”
Section: Summary and Prospectivementioning
confidence: 88%
“…More work is also needed to understand block transport mechanisms in the field and their dependence on slope, erosion rate, and specific factors such as overland flow, soil saturation, and vegetation. While we have shown that blocks affect soil transport by damming, additional feedbacks between the presence of large blocks and soil creep mechanisms should be explored, as well as the effect of different soil flux rules (e.g., Ferdowsi et al, ; Roering, ). Exploration of the relative roles of transport and weathering in producing observed block size distributions through numerical modeling, field studies, and physical experiments would greatly improve our understanding of these landscapes.…”
Section: Discussionmentioning
confidence: 99%